Pengaruh Massa Dan Jenis Pegas Terhadap Konstanta Pegas: Studi Praktikum - Dinaldhi Aditya; Listha Anisha; Aida Fauziah Rahma; Adam Malik (Jurnal Pendidikan Fisika dan Sains (JPFS), 2024)
This research aims to explore the effect of mass and spring type on spring constant through a series of practical experiments. The method used is the experimental method which involves hanging different masses (0.05 Kg, 0.07 Kg, and 0.1 Kg) on three types of springs (strong, medium, and weak) and measuring the change in spring length. The results were analyzed using Hooke's law to determine the spring constant. The data showed that the strong spring had a more stable spring constant compared to the medium and weak springs, which showed greater variation. The spring constant obtained for the strong spring was 10-11 N/m, for the medium spring was 9.24-18.84 N/m, and for the weak spring was 4.71-5.4 N/m. The results support the hypothesis that spring type and load mass affect the spring constant significantly. The strong spring showed higher stability despite the changing load, while the medium and weak spring showed greater variation. These findings are relevant to Hooke's law and provide additional empirical evidence on spring elasticity.